x + 4y – 12 = 0 x = 3y – 7 Which of the following is the resulting equation?

-7y – 19 = 0
y – 5 = 0
7y + 19 = 0
7y – 19 = 0

Respuesta :

Answer:

The answer to your question is  7y - 19 = 0

Step-by-step explanation:

Data

Equation l         x  + 4y - 12 = 0

Equation ll        x = 3y - 7

Process

1.- Substitute equation ll in equation l

                    3y - 7 + 4y - 12 = 0

2.- Group like terms

                   (3y + 4y) + (-7 - 12) = 0

3.- Simplify like terms

                           7y - 19 = 0

4.- Result

                    7y - 19 = 0